Pengujian Karakteristik Pembakaran Bahan Bakar Minyak Pirolisis Plastik Dan Minyak Jelantah Sebagai Bahan Bakar Alternatif - Iko, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
The purpose of this study was to determine the effect of the ratio of used cooking oil on the combustion characteristics of polypropylene (pp) plastic pyrolysis fuel oil. This study used a mixture of used cooking oil and pyrolysis oil of 75%:25%, 50%:50%, and 25%:75%, respectively. The results of mixing the used cooking oil are burned using a combustion container in an open space with. The maximum temperature obtained from each mixture was 20 minutes for a mixture of 75%: 25% used cooking oil, a 50%:50% mixture, 42 minutes for a mixture of 25%:75%. is 34 minutes.Key Words: Used cooking oil, plastic pyroliysis oil.